Formation mechanisms and performance of electrical discharge coatings - Ahmed, Nuhaize (2023)
Electrical discharge coatings (EDCs) are a variant of the electrical discharge machining (EDM) process, and can be applied on complex metal components to repair or act as a protective wear resistant layer. They can be used to make coatings up to several millimetres thickness on electrically conductive substrates using sacrificial electrodes. The technology can be classified under thin EDC, which is a surface modification process, and thick EDC, which is a surface coating process.